1991
DOI: 10.2135/cropsci1991.0011183x003100050030x
|View full text |Cite
|
Sign up to set email alerts
|

Water Relations and Productivity of Alfalfa Leaf Chlorophyll Variants

Abstract: Plant improvement to increase the water‐use efficiency of affalfa (Medicago sativa L.) has been limited. This study compared leaf color variants (pale and dark) to evaluate the effect of alfalfa leaf chlorophyll on water relations and yield of alfalfa. Leaf color populations were selected from ‘Ladak 65’ and visually selected sub‐populations evaluated under controlled‐environment and field conditions. Seven moisture regimes were established in controlled environment studies in which a commercial root medium wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 0 publications
0
24
1
Order By: Relevance
“…The temperature difference exhibited between pale-and normal-green barley was believed to have been mainly the result of increased reflectivity of light from the leaf surface . The lower temperature of pale leaves may also result in significantly lower transpiration rates and, where photosynthetic rates are maintained, greater water use efficient (WUE) (Fisher, 1981 ;Estill et al ., 1991) . The light green genotypes we have studied may also have a similarly high albedo thus minimising the amount of light energy absorbed and reducing leaf temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature difference exhibited between pale-and normal-green barley was believed to have been mainly the result of increased reflectivity of light from the leaf surface . The lower temperature of pale leaves may also result in significantly lower transpiration rates and, where photosynthetic rates are maintained, greater water use efficient (WUE) (Fisher, 1981 ;Estill et al ., 1991) . The light green genotypes we have studied may also have a similarly high albedo thus minimising the amount of light energy absorbed and reducing leaf temperature.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating these physiological activities, N. peltata could maintain its water balance and photosynthesis (Estill et al, 1991;Luquez et al, 1997). Thus, N peltata growing under terrestrial conditions could acclimate to temporarily stressed environments.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that there was more chlorophyll content at rapid grain growth stage, during which there is a great demand for photosynthates and this might help the plant to fix more co2 and meet the increasing demand for photosynthates. Wright and Smith (1983), Ashraf and Khan (1990), Sinha and Patil (1986) and Estill et al (1991) reported a wide variation in chlorophyll contents within species. In the present investigation also the genotypes differed significantly in chlorophyll content.…”
Section: Biophysical and Biochemical Charactersmentioning
confidence: 95%